A picturebook – a pictorial speech act (based on Mum always comes back by Agata Tuszyńska & Iwona Chmielewska) - Wójcicka, Marta (Papers in Linguistics, 2022)
The goal of the article is to provide an analysis of relations between the conventional (verbal) code and the iconic code in a pictorial book called picturebook based on Mum always comes back by Agata Tuszyńska and Iwona Chmielewska. The analysed example is a narrative picturebook that consists of images and text which form two coexisting and correlated modalities adding up to a coherent message. A picturebook is defined as a multimodal text of culture and in the article it is analysed in reference to theories of speech acts and pictures. Detailed consideration concerns elements of the text frame, delimiting elements, motifs (mum, rose, doll), symbols (colour) and narration.